CT Diagnosis of a Thoracic Aort Aneurysm with Type B Aortic Dissection Clinically Misdiagnosed as Acute Pulmonary Embolism - Ahmet Mesrur Halefoglu (Case Reports in Medicine)
A 54-year-old man was admitted to the emergency department, presenting with an acute onset of chest pain and severe respiratory distress symptoms. He was medicated with intravenous analgesia and antihypertensive drugs. The patient was subjected to a chest X-ray which revealed a prominent widening of the mediastinum and pleural effusion on the left side. In laboratory tests-d-dimer level was highly elevated. The patient was clinically interpreted as having an acute pulmonary embolism and referred to the radiology clinic to perform a computed tomography (CT) examination. Contrast-enhanced CT demonstrated that there was no abnormality related to the pulmonary vasculature, but a huge thoracic aorta aneurysm measuring 11 × 8.1 × 7.7 cm in diameter was detected. Accompanying the aneurysm, an intimal flap was also present in the proximal descending thoracic aorta, distal to the origin of the left subclavian artery and extending into the bifurcation level. The patient was therefore diagnosed as having a type B aortic dissection as well. Once these serious conditions were detected, he was immediately transferred to a cardiovascular thoracic surgery hospital for endovascular repairment operation.